VD_FINDINFO HC / 2011 / 710 vom 28. Dezember 2011 - VD Tribunal cantonal (2011)
DROIT DE GARDE, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, INTERNATIONAL | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 48 LDIP, 85 al. 1 LDIP, 2 CLaH 96, 3 CLaH 96, 5 CLaH 96, 308 al. 1 let. b CPC (CH)